ATLAS strategy for primary vertex reconstruction during Run-2 of the LHC. Issue 7 (December 2015) - Borissov, G; Casper, D; Grimm, K; Griso, S Pagan; Pedersen, L Egholm; Prokofiev, K; Rudolph, M; Wharton, A
Abstract: The reconstruction of vertices corresponding to proton-proton collisions in ATLAS is an essential element of event reconstruction used in many performance studies and physics analyses. During Run-1 of the LHC, ATLAS has employed an iterative approach to vertex finding. In order to improve the flexibility of the algorithm and ensure continued performance for very high numbers of simultaneous collisions in Run-2 of the LHC and beyond, a new approach to seeding vertex finding has been developed inspired by image reconstruction techniques. This note provides a brief outline of how reconstructed tracks are used to create an image of likely vertex collisions in an event, describes the implementation in the ATLAS software, and presents some preliminary results of the performance of the algorithm in simulation approximating early Run-2 conditions.